Hand Woven Fabric Learning Resource Management in Surin Province, Banteay Meanchey Province and Champasak District - Wantrong, Associate Professor Dr. Sarapee (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2019)
The purposes of this qualitative and quantitative research were 1) to examine hand woven fabric learning resource management 2) to investigate user satisfaction for hand woven fabric learning resource management and 3) to locate the recommendations for hand woven fabric learning resource management. Research purposive random sampling for qualitative study were 40 librarians, information officers and museum officers. Research samples for quantitative design were 253 service users. There were three distinguish locations as the following: 1) Information and Technology Resource Center in Surindra Rajabhat University, Surin province, Thailand, 2) Library of Meanchey University, Banteay Meanchey province, Kingdom of Cambodia, and 3) Champasak District Museum, Lao People's Democratic Republic. All of them were used by purposive random sampling. Content analysis was used to analyze the content of samples’ feedbacks collected from interview, workshop, group discussion and questionnaire. Percentage, mean, and standard deviation were utilized for statistical analysis. The research results revealed that: 1. Hand woven fabric learning resource management in Surin province, Banteay Meanchey province and Champasak district consisted of supply, quality inspection, analysis and classification, registration, storage, maintenance, survey and sales. 2. The overall user satisfaction of hand woven fabric learning resource management in Surin province, Banteay Meanchey province and Champasak district was at a high level. As considered by the locations, it was found that: 1) In Surin province, hand woven fabrics exhibition received the highest mean satisfaction. 2) In Banteay Meanchey province, hand woven fabric learning resources management received the highest mean satisfaction. And 3) In Champasak district museum, the youth benefit of learning hand woven fabric received the highest mean satisfaction. 3. The recommendations for hand woven fabric learning resource management were 1) permanent exhibition and living exhibition, 2) teaching of hand woven fabric production process, and 3) a curriculum in educational institutes for students and youth to learn weaving for the incessant conservation and inheritance.